Comparison of the effect of transparent film retainer and Hawley retainer - ZHAOXiao⁃ju; ZHAOXiao⁃ying; ZHANG Jin⁃hui (口腔疾病防治, 2017)
Long⁃term stability is an important part of orthodontic treatment and wearing a retainer is one of the meth⁃ ods to keep stable after active orthodontic treatment. Transparent film retainer and Hawley retainer are two kinds of re⁃ tainer usually used in clinical treatment. the previous one is easy to made, comfortable and beautiful to wear, easily damaged. Hawley retainer is relatively complex to made and in a large size. And it is durable and adjustable. However, there are differences between these retainers on the retaining effects in different types of malocclusion. In clinical treat⁃ ment, according to the type of malocclusion, we choose the appropriate retainer to keep stable occlusal relationship after orthodontic treatment.